Method for testing viscosity of polyacrylonitrile spinning stock solution

CN119880707AActive Publication Date: 2025-04-25CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202311392114.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-25
Publication Date
2025-04-25
Estimated Expiration
2043-10-25

AI Technical Summary

Technical Problem

In the prior art, when testing the viscosity of polyacrylonitrile spinning raw liquid, "crusting" is prone to occur, resulting in poor stability and repeatability of the test results and greatly affected by human factors.

Method used

After removing the "crust" on the surface of the stock solution by pretreating the container and stock solution, a solvent of a specific temperature is added to prevent recrust and a viscosity test is performed using an appropriate rotor and test instrument.

Benefits of technology

It effectively reduces the influence of human factors, prevents the "crusting" phenomenon of the stock solution, and improves the stability and repetition of the test results.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004512717620000061
    Figure BDA0004512717620000061
  • Figure BDA0004512717620000071
    Figure BDA0004512717620000071
Patent Text Reader

Abstract

The invention belongs to the technical field of detection methods, and particularly relates to a method for testing the viscosity of a polyacrylonitrile spinning solution. The method for testing the viscosity of the polyacrylonitrile spinning stock solution comprises the following steps: container pretreatment: drying a preparation container, and cooling to room temperature; preparing a spinning solution, namely respectively weighing polyacrylonitrile dry powder and a solvent, and adding into a container; dissolving: dissolving according to dissolving conditions to obtain a stock solution; pretreatment of the stock solution: 'crust 'on the surface layer of the stock solution is removed; viscosity test preparation: selecting a rotor, inserting the rotor into the stock solution, and connecting the rotor with a test instrument through a hook; pretreatment before testing: after the rotor is embedded by the stock solution, adding a solvent; and viscosity testing: starting the testing instrument to carry out viscosity testing, and recording a test result. According to the method for testing the viscosity of the polyacrylonitrile spinning stock solution provided by the invention, the influence of human factors is reduced, the'skinning 'phenomenon of the stock solution is prevented, and the repeatability of a test result is good.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of detection methods, and in particular relates to a method for testing the viscosity of polyacrylonitrile spinning solution. Background Art

[0002] Fiber is a general term for a class of substances and is an apparent form of material existence. It includes natural fibers, chemical synthetic fibers (synthetic polymer fibers), inorganic fibers, and metal fibers. Chemical synthetic fibers have many different properties depending on their raw materials and preparation methods. Organic synthetic fibers can be modified by introducing a variety of active functional groups. Synthetic fibers are made from organic small molecules as monomers, and linear organic polymers are obtained through addition polymerization or condensation polymerization, and are produced through solvent or melt spinning processes. Synthetic fibers are polymer fiber materials. Traditional varieties are mainly divided into the following types according to different skeleton materials: (1) polyester fiber (polyester), (2) polyamide fiber (nylon), (3) polyvinyl alcohol fiber (vinylon), (4) polyacrylonitrile (acrylic), (5) polypropylene fiber (polypropylene), and (6) polyvinyl chloride fiber (chloroprene). Synthetic fiber materials can not only meet the needs of various basic industries in the national economy such as textiles, construction, and plastics, but also have a wider application in many fields such as materials science, life sciences, medicine and health, environmental technology, and aerospace technology. There are many types of synthetic fibers with excellent performance and strong plasticity. Among them, there are more and more reports on the preparation of special functional fibers with excellent performance and specific functions based on polyacrylonitrile fiber.

[0003] In the production of dry acrylic fiber, polyacrylonitrile dry powder needs to be dissolved in the solvent in advance. In the stock solution preparation kettle, polyacrylonitrile and the solvent are fully dissolved and exhausted, then filtered and pressurized, and enter the spinning tunnel. After spinning and washing, the primary silk is obtained. The solid content of the spinning stock solution has a greater impact on the subsequent spinning. If the solid content of the stock solution is high, it will affect the fluidity of the stock solution, making it difficult to filter and affecting the spinnability of the spinning line; if the solid content of the stock solution is low, it will make it difficult to form the primary silk after the spinneret is spun, the amount of drying gas is large, the energy consumption is high, and the fiber yield is affected. The higher the solid content of the stock solution, the greater the viscosity. The viscosity of the stock solution is usually tested in advance to provide guidance for the adjustment of the spinning process parameters. But usually, during the viscosity test of polyacrylonitrile stock solution, the surface of the stock solution that contacts the air is prone to "skinning", that is, a film with a certain strength that is not easy to flow is formed. In particular, the increase in humidity in the air will accelerate the occurrence of the "skinning" phenomenon, that is, water cannot be added after the "skin" of the stock solution is removed. The film produced by the skinning needs to be removed in time before testing, resulting in a large influence of human factors and poor stability of the test results.

[0004] CN107402167A discloses a method for measuring the intrinsic viscosity of polyacrylonitrile-based polymer solution and precursor fiber, which comprises preparing high molecular polymer solutions of different concentrations, measuring their specific viscosity, measuring the specific viscosity of the polymer solution to be measured, and calculating the intrinsic viscosity of the polymer solution; a series of polymer concentration solutions are used, and for polymers with high molecular weight and long molecular chains, more dilute solutions are prepared accordingly, while for polymers with low molecular weight and short molecular chains, higher concentration solutions are prepared for measurement, thereby expanding the practical applicability of the method. The Wushi viscometer method requires a low sample concentration.

[0005] CN113740285A discloses a method for testing the solid content of polyacrylonitrile spinning solution, wherein the polyacrylonitrile mass fraction of the polyacrylonitrile spinning solution is diluted to 0.30% to 2.00% by using dimethyl sulfoxide, and then the absorbance at the maximum absorption wavelength of the diluted polyacrylonitrile spinning solution is detected by ultraviolet-visible spectrophotometry, the maximum absorption wavelength does not change with the change of the polyacrylonitrile mass fraction, and the absorbance at the maximum absorption wavelength of the diluted polyacrylonitrile spinning solution has a good linear relationship with the polyacrylonitrile mass fraction, and the linear correlation coefficient is greater than 0.999. This requires a dilute solution, that is, a low sample concentration, and the solid content is measured, and the viscosity is not detected.

[0006] In the open paper "Study on the viscosity characteristics of polyacrylonitrile aqueous precipitation polymerization and its spinning solution Wu Jiwei 20090420 Shandong University", the effect of molecular weight on viscosity was measured by a rotational viscometer, and the temperature was increased by 10°C every 20 minutes. The temperature increase method was used to test the viscosity at different temperatures, but the problem of skinning in practical applications was not eliminated. Summary of the invention

[0007] The technical problem to be solved by the present invention is to overcome the above-mentioned defects of the prior art and provide a method for testing the viscosity of polyacrylonitrile spinning solution, thereby reducing the influence of human factors, preventing the "skinning" phenomenon of the solution, and achieving good repeatability of the test results.

[0008] The method for testing the viscosity of polyacrylonitrile spinning solution of the present invention comprises the following steps:

[0009] (1) Container pretreatment: Dry the preparation container and cool it to room temperature;

[0010] (2) Preparation of spinning solution: Weigh polyacrylonitrile dry powder and solvent respectively and add them into a container;

[0011] (3) Dissolving: dissolving at a certain temperature to obtain a stock solution;

[0012] (4) Stock solution pretreatment: remove the "skin" on the surface of the stock solution;

[0013] (5) Preparation for viscosity test: Select a rotor, insert the rotor into the stock solution, and connect it to the test instrument with a hook;

[0014] (6) Pretreatment before testing: After the stock solution has embedded the rotor, add the solvent;

[0015] (7) Viscosity test: Start the test instrument to perform viscosity test and record the test results.

[0016] The drying temperature of step (1) is 100-120° C., and the drying time is 1-2 h. The drying temperature is preferably 100° C., and the drying time is preferably 2 h.

[0017] The mass ratio of the polyacrylonitrile dry powder and the solvent in step (2) is 1:2.05 to 1:3.0, preferably 1:2.3 to 1:2.4.

[0018] The solvent used in step (2) and step (6) is dimethylacetamide.

[0019] The rotor model selected in step (5) is a 29# rotor with a viscosity range of 50,000-100,000 mPa·s and a rotation speed of 10 rpm.

[0020] The temperature of the solvent added in step (6) is 25°C to 50°C lower than the dissolution temperature in step (3), that is, the temperature is 65°C to 40°C.

[0021] The temperature of the viscosity test in step (7) is kept consistent with the solvent temperature.

[0022] The mass of the solvent added in step (6) is 2.0% to 10.0% of the total mass of the stock solution, preferably 2.5% to 5.0%.

[0023] The dissolution temperature in step (3) is 90° C., the dissolution time is 4 h, and the dissolution method is preferably heating in a water bath.

[0024] The testing instrument is NDJ-1C rotational viscometer.

[0025] Specifically, the method for testing the viscosity of polyacrylonitrile spinning solution comprises the following steps:

[0026] (1) Container pretreatment: Dry the preparation container in an oven at 100°C for 2 h and cool to room temperature;

[0027] (2) Preparation of spinning solution: Weigh polyacrylonitrile powder and solvent dimethylacetamide in a mass ratio of 1:2.3 to 1:2.4 and add them into a container;

[0028] (3) Dissolving: Heat in a water bath to 90°C for 4 h to obtain a stock solution;

[0029] Slowly add polyacrylonitrile powder into the solvent, stir thoroughly until no obvious white particles are present, seal the container, and dissolve at 90°C for 4 hours without stirring.

[0030] (4) Pretreatment of stock solution: Use tweezers to peel off the "crust" on the surface of the stock solution and remove it;

[0031] (5) Preparation for viscosity test: Select a 29# rotor, insert the rotor into the stock solution until the rotor is inserted into the center of the stock solution, and connect it to the test instrument with a hook;

[0032] (6) Pretreatment before testing: After the stock solution has embedded the rotor, add 2.0% to 10.0% of the solvent dimethylacetamide;

[0033] (7) Viscosity test: When the relative humidity of the air is 30-40% or 70-80%, start the test instrument and complete the test within 1 minute. Record multiple test results.

[0034] The solvent in step (2) of the present invention is the same as the solvent in step (6). After the polyacrylonitrile stock solution is prepared, it forms a colloid state. The solvent added later will not dissolve immediately and will not affect the viscosity test of the center of the stock solution in a short time. After adding the solvent, the viscosity test needs to be performed immediately (2-10s). The temperature of the viscosity test is consistent with the dissolution temperature. And step (5) needs to estimate the viscosity of the stock solution, and select a suitable rotor and speed according to the viscosity range of the stock solution. In the present invention, a 29# rotor with a speed of 10 rpm is used, which is suitable for a rotor with a viscosity range of 50000-100000 mPa·s.

[0035] In the pretreatment process before the test, the present invention can effectively isolate the stock solution from the air after adding the solvent, prevent the "skinning" phenomenon from occurring, and objectively improve the test stability. At the same time, the addition of solvent to the stock solution will inevitably affect the change of the stock solution properties. Within the allowed test time, as long as its main impact range does not affect the stock solution properties around the rotor, the reliability of the stock solution viscosity test results can be guaranteed. Therefore, there are requirements for the temperature and dosage of the added solvent. The higher the temperature of the added solvent and the larger the dosage, the more likely it is that the solid content of the stock solution will drop faster, affecting the viscosity test results; the lower the temperature of the added solvent, the more likely it is that the temperature of the stock solution will drop, causing the viscosity of the stock solution to increase; if too little solvent is added, it will not play an isolation role.

[0036] Compared with the prior art, the present invention has the following beneficial effects:

[0037] Compared with the traditional viscometer detection method, the test method for the viscosity of the polyacrylonitrile spinning solution of the present invention can solve the problem of the "skin" affecting the test result again during the test process after the "skin" is removed. After the "skin" is removed, a solvent at a specific temperature is added, which is not easy to form a skin again. The method has good adaptability to the humidity in the environment and good stability and repeatability of the test results. DETAILED DESCRIPTION

[0038] The present invention is further described below by means of specific examples, but the examples do not limit the present invention.

[0039] The viscosity of the stock solution in the examples of this specification is the rotational viscosity. The instrument used for the test is NDJ-1C rotational viscometer, the equipment manufacturer is Shanghai Changji Geological Instrument Co., Ltd., the rotor uses a 29# rotor, and the test is repeated three times. The density of dimethylacetamide is 0.937 g / cm 3 .

[0040] The polyacrylonitrile dry powder is a binary copolymer of acrylonitrile and methyl acrylate, wherein the mass content of acrylonitrile is 93.95%, the mass content of methyl acrylate is 6.05%, the number average molecular weight of the copolymer is 32919, and the molecular weight distribution width is 2.88.

[0041] Example 1

[0042] The method for testing the viscosity of polyacrylonitrile spinning solution comprises the following steps:

[0043] (1) Container pretreatment: Dry the preparation container in an oven at 100°C for 2 h and cool to room temperature;

[0044] (2) Preparation of spinning solution: 61 g of polyacrylonitrile dry powder and 139 g of dimethylacetamide solvent were weighed and added into a container;

[0045] (3) Dissolving: Place the glass beaker containing the spinning solution in a water bath and heat it to 90°C to obtain the solution;

[0046] (4) Stock solution pretreatment: removal of the "skin" on the surface of the stock solution;

[0047] (5) Preparation for viscosity test: Select a 29# rotor, insert the rotor into the stock solution, and connect it to the test instrument with a hook;

[0048] (6) Pretreatment before testing: After the stock solution has embedded the rotor, add 5 mL of 60°C solvent dimethylacetamide;

[0049] (7) Viscosity test: When the relative humidity of the air is 30-40%, start the test instrument and record the test results three times.

[0050] Example 2

[0051] The method for testing the viscosity of polyacrylonitrile spinning solution comprises the following steps:

[0052] (1) Container pretreatment: Dry the preparation container in an oven at 100°C for 2 h and cool to room temperature;

[0053] (2) Preparation of spinning solution: 61 g of polyacrylonitrile dry powder and 139 g of dimethylacetamide solvent were weighed and added into a container;

[0054] (3) Dissolving: Place the glass beaker containing the spinning solution in a water bath and heat it to 90°C to obtain the solution;

[0055] (4) Stock solution pretreatment: removal of the "skin" on the surface of the stock solution;

[0056] (5) Preparation for viscosity test: Select a 29# rotor, insert the rotor into the stock solution, and connect it to the test instrument with a hook;

[0057] (6) Pretreatment before testing: After the stock solution has embedded the rotor, add 5 mL of 60°C solvent dimethylacetamide;

[0058] (7) Viscosity test: When the relative humidity of the air is 30-40%, start the test instrument and record the test results three times.

[0059] Example 3

[0060] The method for testing the viscosity of polyacrylonitrile spinning solution comprises the following steps:

[0061] (1) Container pretreatment: Dry the preparation container in an oven at 100°C for 2 h and cool to room temperature;

[0062] (2) Preparation of spinning solution: 61 g of polyacrylonitrile dry powder and 139 g of dimethylacetamide solvent were weighed and added into a container;

[0063] (3) Dissolving: Place the glass beaker containing the spinning solution in a water bath and heat it to 90°C to obtain the solution;

[0064] (4) Stock solution pretreatment: removal of the "skin" on the surface of the stock solution;

[0065] (5) Preparation for viscosity test: Select a 29# rotor, insert the rotor into the stock solution, and connect it to the test instrument with a hook;

[0066] (6) Pretreatment before testing: After the stock solution has embedded the rotor, add 5 mL of 60°C solvent dimethylacetamide;

[0067] (7) Viscosity test: When the relative humidity of the air is 30-40%, start the test instrument and record the test results three times.

[0068] Example 4

[0069] The method for testing the viscosity of polyacrylonitrile spinning solution comprises the following steps:

[0070] (1) Container pretreatment: Dry the preparation container in an oven at 100°C for 2 h and cool to room temperature;

[0071] (2) Preparation of spinning solution: 61 g of polyacrylonitrile dry powder and 139 g of dimethylacetamide solvent were weighed and added into a container;

[0072] (3) Dissolving: Place the glass beaker containing the spinning solution in a water bath and heat it to 90°C to obtain the solution;

[0073] (4) Stock solution pretreatment: removal of the "skin" on the surface of the stock solution;

[0074] (5) Preparation for viscosity test: Select a 29# rotor, insert the rotor into the stock solution, and connect it to the test instrument with a hook; (6) Pretreatment before testing: After the stock solution has embedded the rotor, add 5 mL of 60°C solvent dimethylacetamide; (7) Viscosity test: When the relative humidity of the air is 30-40%, start the test instrument and record the results of three experiments.

[0075] Example 5

[0076] The method for testing the viscosity of polyacrylonitrile spinning solution comprises the following steps:

[0077] (1) Container pretreatment: Dry the preparation container in an oven at 100°C for 2 h and cool to room temperature;

[0078] (2) Preparation of spinning solution: 61 g of polyacrylonitrile dry powder and 139 g of dimethylacetamide solvent were weighed and added into a container;

[0079] (3) Dissolving: Place the glass beaker containing the spinning solution in a water bath and heat it to 90°C to obtain the solution;

[0080] (4) Stock solution pretreatment: removal of the "skin" on the surface of the stock solution;

[0081] (5) Preparation for viscosity test: Select a 29# rotor, insert the rotor into the stock solution, and connect it to the test instrument with a hook; (6) Pretreatment before testing: After the stock solution has embedded the rotor, add 5 mL of 60°C solvent dimethylacetamide; (7) Viscosity test: When the relative humidity of the air is 30-40%, start the test instrument and record the results of three experiments.

[0082] Example 6

[0083] The method for testing the viscosity of polyacrylonitrile spinning solution comprises the following steps:

[0084] (1) Container pretreatment: Dry the preparation container in an oven at 100°C for 2 h and cool to room temperature;

[0085] (2) Preparation of spinning solution: 61 g of polyacrylonitrile dry powder and 139 g of dimethylacetamide solvent were weighed and added into a container;

[0086] (3) Dissolving: Place the glass beaker containing the spinning solution in a water bath and heat it to 90°C to obtain the solution;

[0087] (4) Stock solution pretreatment: removal of the "skin" on the surface of the stock solution;

[0088] (5) Preparation for viscosity test: Select a 29# rotor, insert the rotor into the stock solution, and connect it to the test instrument with a hook; (6) Pretreatment before testing: After the stock solution has embedded the rotor, add 5 mL of 60°C solvent dimethylacetamide; (7) Viscosity test: When the relative humidity of the air is 30-40%, start the test instrument and record the results of three experiments.

[0089] Example 7

[0090] The method for testing the viscosity of polyacrylonitrile spinning solution comprises the following steps:

[0091] (1) Container pretreatment: Dry the preparation container in an oven at 100°C for 2 h and cool to room temperature;

[0092] (2) Preparation of spinning solution: 61 g of polyacrylonitrile dry powder and 139 g of dimethylacetamide solvent were weighed and added into a container;

[0093] (3) Dissolving: Place the glass beaker containing the spinning solution in a water bath and heat it to 90°C to obtain the solution;

[0094] (4) Stock solution pretreatment: removal of the "skin" on the surface of the stock solution;

[0095] (5) Preparation for viscosity test: Select a 29# rotor, insert the rotor into the stock solution, and connect it to the test instrument with a hook;

[0096] (6) Pretreatment before testing: After the stock solution has embedded the rotor, add 5 mL of 60°C solvent dimethylacetamide;

[0097] (7) Viscosity test: When the relative humidity of the air is 30-40%, start the test instrument and record the test results three times.

[0098] Comparative Example 1

[0099] This comparative example is the same as Example 1, except that step (6) is removed.

[0100] Comparative Example 2

[0101] This comparative example is the same as Example 1, except that the relative humidity of the air is adjusted to 70-80%, and the operation of step (6) is removed.

[0102] Comparative Example 3

[0103] This comparative example is the same as Example 1, except that 8 mL of dimethylacetamide at 35° C. was used in step (6).

[0104] Comparative Example 4

[0105] This comparative example is the same as Example 1, except that 8 mL of dimethylacetamide at 65° C. is used in step (6).

[0106] Comparative Example 5

[0107] This comparative example is the same as Example 1, except that 4 mL of dimethylacetamide at 55° C. is used in step (6).

[0108] Comparative Example 6

[0109] This comparative example is the same as Example 1, except that 20 mL of dimethylacetamide at 55° C. is used in step (6).

[0110] The test results of the above embodiments and comparative examples are shown in Table 1.

[0111] Table 1 Test results

[0112]

[0113]

[0114] Of course, the above contents are only preferred embodiments of the present invention and cannot be considered to limit the scope of the embodiments of the present invention. The present invention is not limited to the above examples, and equal changes and improvements made by ordinary technicians in the technical field within the essential scope of the present invention should all fall within the scope of the patent coverage of the present invention.

Claims

1. A method for testing the viscosity of polyacrylonitrile spinning solution, characterized in that: The following steps are involved: (1) Container pretreatment: Dry the preparation container and cool it to room temperature; (2) Preparation of spinning solution: Weigh polyacrylonitrile dry powder and solvent respectively and add them into a container; (3) Dissolving: dissolving at a certain temperature to obtain a stock solution; (4) Stock solution pretreatment: remove the "skin" on the surface of the stock solution; (5) Preparation for viscosity test: Select a rotor, insert the rotor into the stock solution, and connect it to the test instrument with a hook; (6) Pretreatment before testing: After the stock solution has embedded the rotor, add the solvent; (7) Viscosity test: Start the test instrument to perform viscosity test and record the test results.

2. The method for testing the viscosity of polyacrylonitrile spinning solution according to claim 1, characterized in that: The drying temperature of step (1) is 100-120° C., and the drying time is 1-2 hours.

3. The method for testing the viscosity of polyacrylonitrile spinning solution according to claim 1, characterized in that: The mass ratio of the polyacrylonitrile dry powder and the solvent in step (2) is 1:2.05 to 1:3.

0.

4. The method for testing the viscosity of polyacrylonitrile spinning solution according to claim 1, characterized in that: The solvent used in step (2) and step (6) is dimethylacetamide.

5. The method for testing the viscosity of polyacrylonitrile spinning solution according to claim 1, characterized in that: The rotor model selected in step (5) is a rotor having a viscosity measurement range of 50,000-100,000 mPa·s.

6. The method for testing the viscosity of polyacrylonitrile spinning solution according to claim 1, characterized in that: The temperature of the solvent added in step (6) is 25°C to 50°C lower than the dissolution temperature in step (3).

7. The method for testing the viscosity of polyacrylonitrile spinning solution according to claim 6, characterized in that: The temperature of the viscosity test in step (7) is kept consistent with the solvent temperature.

8. The method for testing the viscosity of polyacrylonitrile spinning solution according to claim 6, characterized in that: The mass of the solvent added in step (6) is 2.0% to 10.0% of the total mass of the stock solution.

9. The method for testing the viscosity of polyacrylonitrile spinning solution according to claim 6, characterized in that: The dissolution temperature in step (3) is 90°C.

10. The method for testing the viscosity of polyacrylonitrile spinning solution according to claim 6, characterized in that: The testing instrument is NDJ-1C rotational viscometer.

Citation Information

Patent Citations

  • Method for testing solid content of polyacrylonitrile spinning stock solution

    CN113740285A

  • Carbon fiber spinning solution de-bubbling method

    CN103422179A

  • Method for measuring viscosity of substrate support polymer film

    CN105675442A

  • Measurement method of intrinsic viscosity of polyacrylonitrile-based polymer solutions and protofilaments

    CN107402167A

  • Shearing viscosity estimation method and rheogram creation method

    JP2011069754A